Performance evaluation and challenges for implementing e-GP : a case of roads & highways department, Bangladesh - Biswas, Munmun (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.